Investigations on the corrosion of 316L steel composite materials with MgO/TiO2 ceramic immersed in molten cryolite - C. Weigelt; S. Yaroshevskyi; F. Kerber; N. Brachhold; T. Zienert; A. Adamczyk; D. Vogt; A. Charitos; C.G. Aneziris (Open Ceramics, 2023)
Composites based on a steel with 40 vol% magnesia or titania were produced with the ceramics-derived extrusion and pressureless sintering. The materials were tested in a laboratory-scale fused-salt electrolysis cell with a synthetic cryolite in order to identify their potential use as electrode material in the Hall-Héroult process. The highly corrosive atmosphere and salt melt initiated certain corrosion effects in both material variants. The corrosion depth was determined with 1160 μm for magnesia and 463 μm for titania, respectively, after 8 h corrosion test. The initial corrosion includes the complete penetration of the specimens with cryolite and the dissolution of the ceramic component. A pre-oxidation of the specimens containing magnesia depressed the corrosion depth by 75% due to the formation of an aluminium oxide layer in the composite material during corrosion tests. The reduction in corrosion depth by pre-oxidation was less pronounced for the TiO2 composite materials (−15%).